Mācību procesa individualizācija latviešu valodas apguvē mazākumtautību vidusskolā - Drakša, Ludmila (Latvijas Universitāte, 2006)
Ludmila Drakša. Mācību procesa individualizācija latviešu valodas apguvē mazākumtautību vidusskolā. Mācību procesa individualizācija dod iespēju apgūt latviešu valodu kvalitatīvi. Pētījuma mērķis ir teorētiski pamatot un eksperimentāli pārbaudīt mācību procesa individualizācijas efektivitāti latviešu valodas apguvē mazākumtautību vidusskolā. 1. daļā aplūkoti mācību procesa individualizācijas teorētiskie aspekti, izskatīti pedagoģiski psiholoģiskie pamati. Parādītas mācību procesa individualizācijas iespējas latviešu valodas apguves procesā. 2. daļā veikti praktiskie pētījumi mācību procesa individualizācijas ieviešanā latviešu valodas apguvē mazākumtautību vidusskolā: izstrādāts modelis un izveidota didaktisko uzdevumu sistēma mācību procesa individualizācijas īstenošanai latviešu valodas stundās. Darbā tika raksturots eksperimenta klases skolēnu latviešu valodas prasmes līmenis un viņu individuālās īpatnības eksperimenta sākuma un nobeiguma stadijā, veikta izstrādātās metodikas efektivitātes analīze.

Ludmila Draksha. “Individualization of Teaching/Learning Process for the Latvian Language Acquisition in Secondary Schools” Individualization of teaching/learning process offers more efficient methods for acquisition of the Latvian language. The aim of this paper is to prove theoretically and try experimentally the efficiency of teaching/learning process individualization for acquisition of the Latvian language at national minorities secondary schools. The first part of this paper highlights the theoretical and psychological aspects of the teaching/learning process individualization. The concept and the aim of this process as well as the methods for determining the students’ individual skills are considered in this paper. The author of this paper not only reviews the potentials for the teaching/learning process individualization and the criteria for the Latvian language acquisition assessment but also characterizes the Latvian language acquisition level of the experimental group as well as their individual features at the initial stage. The second part of this paper highlights the practical aspects related to the introduction of the individualization of teaching/learning process for acquisition of the Latvian language at national minorities secondary schools. The author has elaborated both the model of teaching/learning process individualization and the corresponding system of didactic exercises. This part of the paper characterizes the Latvian language acquisition level of the experimental group and their individual features at the final stage of the experiment and analyses the efficiency of the methods mentioned.
Possibilities of individualizing the teaching- learning process for Latvian language acquisition at minority language secondary school
Keywords: Pedagoģija